(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2025)
The reproductive biology of Melanophryniscus devincenzii was described here, based on morphometrics and gonadal analysis of 86 individuals collected in the Sertão Municipal Natural Park, Rio Grande do Sul, Brazil. Individuals were captured both manually and using pitfall traps. We identified 63 males and 23 females, with the sex ratio biased towards males. Sexual dimorphism was observed, with females being larger than males. No significant correlation was found between female body size and oocyte number, nor between male body size and testicular mass, indicating that energetic investment may be more focused on reproduction than on growth. All analyzed females (except one) exhibited mature oocytes, immature and atretic oocytes in their ovaries, suggesting that females may be latent to reproductive event. This reproductive latency benefit to those species that have explosive reproductive events and depend on rainfall.